Membangun Keterampilan Pendidik Melalui Pelatihan Pembuatan Media Pembelajaran Berbasis Artificial Intelligence - Andi Baso Kaswar; Nurjannah; Meisaraswaty Arsyad; Dewi Fatmarani Surianto; Rosidah (Sakura Digital Nusantara, 2023)
In this digital era, artificial intelligence (AI) technology plays a crucial role in driving innovation in the education sector. This article discusses efforts to address challenges in understanding and practical skills among educators regarding the implementation of AI in learning. The focus is on training conducted at SMP Negeri 2 Kahu, which faces challenges in using AI to enhance the quality of learning media. The training begins with a basic understanding of AI, involving definitions, fundamental concepts, recent developments, and ethical aspects of AI usage. The final session of the training emphasizes the utilization of AI in developing interactive and adaptive learning media, particularly using Chat GPT. Participants engage in practical demonstrations and collaborative discussions to design the integration of this technology into the learning process. Post-training evaluations indicate an improvement in participants' understanding, although challenges in technology access need to be addressed. This training is expected to stimulate innovation, create an adaptive educational ecosystem, and provide a relevant and adaptive learning experience for students in the digital era.